2021
DOI: 10.1177/21582440211014520
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Donation Behavior in Medical Crowdfunding in Social Media

Abstract: Medical crowdfunding in social media is growing to be a convenient, accessible, and secure manner to cover medical expenses. It differs from traditional donation initiatives and medical crowdfunding on non-social media platforms in that projects are disseminated via social media network and among acquaintances. Through semi-structured in-depth interviews on donation behaviors of 52 respondents, this study uses grounded theory to extract seven main categories that affect medical crowdfunding donation behavior i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
9
1
Order By: Relevance
“…However, although we expected that photos would increase trust and in turn lead to greater donations in H2c, more photos were found to lead to a smaller average donation amount. Although photos in reward‐based crowdfunding increased trust (Duarte et al, 2012; Wang et al, 2017) and trust has been found to have a positive impact on donation behavior (Huang et al, 2021; Q. Li, 2017; Sargeant & Lee, 2004), this work found the opposite direction. One possible reason for the negative direction is that the number of photos could be highly correlated with whether campaign organizers are individuals (fewer photos) or organizations (more photos) and the direction may be picking up the effect of whether organizers are individuals or organizations, rather than one with the number of photos.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, although we expected that photos would increase trust and in turn lead to greater donations in H2c, more photos were found to lead to a smaller average donation amount. Although photos in reward‐based crowdfunding increased trust (Duarte et al, 2012; Wang et al, 2017) and trust has been found to have a positive impact on donation behavior (Huang et al, 2021; Q. Li, 2017; Sargeant & Lee, 2004), this work found the opposite direction. One possible reason for the negative direction is that the number of photos could be highly correlated with whether campaign organizers are individuals (fewer photos) or organizations (more photos) and the direction may be picking up the effect of whether organizers are individuals or organizations, rather than one with the number of photos.…”
Section: Discussionmentioning
confidence: 58%
“…Many prior studies have suggested that trust positively influences donation behavior (Huang et al, 2021; Li, 2017; Sargeant & Lee, 2004). In‐depth interviews of donors who have used donation‐based crowdfunding revealed that perceived trust has a significant impact on donation behavior (Huang et al, 2021). Trust is one of the most important factors that influence online donation decisions (Li, 2017).…”
Section: Theoretical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The success factors involve the main actors in the whole medical crowdfunding campaigns, but campaign factors were more frequently studied than other factors. Platform factors, however, played an important role in medical crowdfunding [ 47 ], because platforms are important in linking donors and raisers [ 48 ]. There were relatively few studies related to donors; thus, future studies could pay more attention to this area.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors have been shown to affect the output of a single initiative dramatically. These range from interpersonal relationships (social media presence and contact networks), reciprocity in helping, attitude towards donating (target audience), perceived control of behaviour, perceived trust, project information and the patients’ characteristics (Huang et al 2021 ; Xing et al 2021 ). In China, medical information (low mortality rate, high frequency) and epidemiological details about the campaigners and clinical cases were found to be among the most reliable determinants of success, and the same holds for some demographic and social attributes, like age and location (Ba et al 2021 ).…”
Section: Concept Mapping and Discussionmentioning
confidence: 99%